Investigation of Sulfur(VI) Chemistry - Mendonca Matos, Priscilla (2019)
This thesis focuses closely on the latest advancements in the synthesis of sulfur(VI) analogues, namely sulfonimidates and sulfoximines. A detailed analysis of their applications and syntheses is reported into two sections: synthesis of racemic sulfoximines from acyclic sulfonimidates, and secondly, the synthesis of enantioenriched NH-sulfoximines from cyclic sulfonimidates.